Investigation of the Effect of Larestan’s Pipeline Water on the Mechanical Properties of Concretes Containing Granite Aggregates - Masoud Forsat; S. S. Mirjavadi; A. M. S. Hamouda (Advances in Civil Engineering)
In this study, the compressive strength of the concretes made by the pipeline water of Larestan has been investigated. Although the used water for the concretes must be clean, standard, and generally drinkable water, in Larestan city, the pipeline water is nonpotable water; meanwhile, this type of water is still being used in the mixture of the concretes by companies and contractors. Since in the initial tests the compressive strength of the normal samples did not satisfy the standards, 50% of granite aggregate was replaced with the purpose of increasing strength of the samples. Then four types of samples were made, which are (1) normal concrete with pipeline water, (2) normal concrete with potable water, (3) granite concrete with pipeline water, and (4) granite concrete with potable water. The results showed that the compressive strength of normal samples is not standard in the case of using the pipeline water. This issue can be seen during the first four weeks of the samples, whereas these samples are placed in the standard zone by replacing 50% of granite aggregate instead of normal aggregates. This may be attributed to the compensating effect of granite aggregates in opposition to damaging effect of water. Also, by using the granite aggregates in the mixture, the compressive strengths of the samples were standard and almost identical in both cases of pipeline water and tap water. As a result, the concretes made in this city must include additives for increasing the strength, or the tap water should be used as a replacement for pipeline water.